Risky moms, risky kids? Fertility and crime after the fall of the wall - Arnaud Chevalier; Olivier Marie (Tinbergen Institute, 2019)
We study the link between parental selection and child criminality. Following the collapse of the communist regime in 1989, the number of births halved in East Germany. These cohorts became markedly more likely to be arrested as they grew up in reunified Germany. This is observed for both genders and all offence types. We highlight risk attitude as an important reason why certain women did not alter their fertility decisions during this time of economic uncertainty. We also show that this preference for risk was then strongly transmitted to their children which may in turn explain their high criminal propensity.
Keywords: K42; J13; 330; Fertility; crime; parental selection; economic uncertainty; risk attitude